Persepsi Guru Terhadap Implementasi Kurikulum Merdeka dalam Pembelajaran PAI dan Budi Pekerti di Sekolah Dasar - Zuhriyyah Hidayati; Nurdi Nurdi (Fakultas Agama Islam Universitas Billfath, 2023)
This study aims to describe the perceptions of Islamic Religious Education teachers towards the implementation of the Kurikuulum Merdeka in PAI dan Budi Pekerti learning activities. The method used is the descriptive method. Using a purposive sampling technique, the research sample consisted of 21 Islamic Religious Education teachers and Elementary School Budi Pekerti in Turi District. Data on teacher perceptions were collected through questionnaires and interviews. The data collected was then analyzed by descriptive analysis. The results showed that most of the participants (85.7%) agreed to the implementation of the Kurikulum Merdeka in schools and acknowledged the advantages contained in the Kurikulum Merdeka, but only some (39.5%) of the participants were able to understand and apply the key concepts in learning activities consistently. This is because participants experience difficulties understanding learning outcomes, reducing CP to TP and ATP, as well as difficulties in preparing lesson plans/modules, and assessments based on the Kurikulum Merdeka. Another obstacle is the limited facilities and infrastructure and teachers’ low IT ability. These findings indicate that socialization and training on the Kurikulum Merdeka alone are not enough, but there needs to be a consistent mentoring program for teachers so that they can implement the Kurikulum Merdeka in the teaching and learning process consistently.